Integrasi Digital Tools dalam Strategi Digipreneur: Peran Google Business Profile, TikTok, TikTok Ads, dan Landing Page dalam Customer Journey UMKM - Yola Ervilia; Febriyansyah Ramadhan (Jurnal Bisnis, Manajemen, dan Ekonomi, 2026)
Changes in consumer behavior have encouraged micro, small, and medium enterprises (MSMEs) to manage digital touchpoints in a more integrated manner. This study analyzes the functions, interrelationships, and contributions of Google Business Profile, TikTok, TikTok Ads, and Google Sites or landing pages in supporting digipreneur marketing communication strategies. The study employed an integrative literature review with a qualitative approach. Academic literature published between 2021 and 2026 was identified through Google Scholar, Garuda, the Directory of Open Access Journals, and Crossref, and was selected through identification, screening, eligibility assessment, and final inclusion. The selected literature was analyzed through coding and thematic synthesis. The findings show that the four digital tools perform distinct but complementary functions. Google Business Profile strengthens local visibility and trust through business information and customer reviews. TikTok facilitates brand discovery, audience engagement, and community formation, while TikTok Ads expands reach and improves promotional targeting. Google Sites or landing pages serve as information hubs and conversion points. Their integration across the customer journey connects discovery, search, consideration, action, and post-purchase stages. The effectiveness of a digital strategy therefore depends not on the number of platforms used, but on functional alignment, information consistency, content quality, responsible data management, and the MSMEs' ability to evaluate marketing outcomes.